Direito à participação pública indígena no aproveitamento hidrelétrico de Belo Monte - Bacovis, Maria Cristina Martins de Figueiredo (2013)
The proposed of Belo Monte hydroelectric use, on the Xingu River in the Pará state, is a priority in the Accelerated Growth Plan of the Brazilian federal government and when completed will be the third largest dam in the world. Positions assumed in our country, about the construction of Belo Monte, are diametrically opposed and that has caused a series of legal and administrative discussions. A project of this proportion takes to the discussion of public participation in environmental licensing processes of large enterprises. In this context, this thesis has as its object the study of public participation of indigenous peoples in the Belo Monte hydroelectric implementation process. The use of the hypothetical-deductive approach promoted the object of study, enabling the achievement of the general objective of the research, which is to situate and understand the level of public participation of indigenous peoples in the implementation of the Belo Monte project. For the development of the dissertation it was used the bibliographic and documentary research as technical procedure. The thematic development directed to the analysis of the ILO 169 Convention, which recognizes the right of indigenous and tribal peoples to be free and informed consulted before decisions affecting their rights be deliberate. The research is structured on the following categories of analysis: human rights, social and environmental impacts and public participation, highlighting indigenous participation as a fundamental human right, seeking to broaden the debate on current and controversial issue, as is the Belo Monte hydroelectric. This work is divided into three sections: The Recognition of indigenous rights, The Belo Monte concerns and The Public participation in Belo Monte hydroelectric, which identifies the major conceptual elements of public participation, clarifies the public hearings and discusses the indigenous peoples trajectory in the struggle for their rights recognition, especially their (non) participation in the implementation of Belo Monte. The present research found that the Belo Monte Hydroelectric is being built, even without indigenous participation in its implementation, and other government actions are being taken in order to reduce the rights of indigenous peoples to their lands.